Emily Dickinson : poetry for kids - Dickinson, Emily, 1830-1886 (MoonDance, 2016)
Introduces younger audiences to the poetry of Emily Dickinson through thirty-five signature works complemented by explanatory text, definitions of important words, and illustrations.